How SMEs or larger firms and industries' productivity respond to technology: a panel data study - Elias Sanidas (SPOUDAI - Journal of Economics and Business, 2014)
This paper is an important and necessary extension of the recent study by Lim and Sanidas (2011) where it was rigorously shown that both types of technology positively affect firms and industries in South Korea. How is this technological impact differentiated between SMEs and larger firms? The present paper answers this question and provides policy recommendations accordingly. Following the same methodology as in the just mentioned study, we put emphasis on the role of technological innovations which consist of two components: technical innovations (TIs) and organizational innovations (OIs). We use firm based data and the econometric method of Fixed Effects (FE) to measure the relationship between OIs, TIs and productivity. In these regressions we included some standard control variables such as wage efficiency, educational level, and capital to labor ratio to accommodate for other important influences. Some industries such as electrical machinery, motor vehicles, and non-electrical machinery have become more efficient in terms of OIs and TIs and thus improved productivity considerably. The results indicate that in general the size of firms is rather neutral to the influence of technology and all other factors on productivity. Thus, overall SMEs as well as large firms behave similarly in terms of the established relationships in this paper. However some significant differences which are detected in this study still exist.
Keywords: C23; L23; O33; 330; organizational and technical innovations; technology; Just-in-time; panel data; SMEs